Numerical analysis of surface cracks repaired with single and double patches of composites - Iváñez, Inés (2018)
In this work, the performances of circular single- and double-sided composite patch repairs are compared by computing the maximum stress intensity factor of a repaired surface crack. The three-dimensional finite-element method is used to calculate the stress intensity factor along the crack. The effects of the crack depth, composite patch thickness and patch material on the stress intensity factor variation are highlighted. The obtained results show that the selection of single- or double-sided patches depends on both the crack depth and patch thickness.